2012
DOI: 10.1007/s13224-012-0257-2
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia in Hypertensive Disease of Pregnancy

Abstract: Background Thrombocytopenia is defined as a platelet count of less than 150 9 10 3 ll. It is commonly diagnosed and has attracted more interest from the researchers in pregnant women during the last 20 years, especially in hypertensive pregnant women. Aim To assess the incidence of thrombocytopenia in hypertensive pregnant women during the third trimester of pregnancy. Methods Five hundred forty-four pregnant women were included in this study from a total of 10,272 admitted at the Obstetrics and Gynecology Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
(20 reference statements)
2
11
1
1
Order By: Relevance
“…23,28 [9][10][11]14,21 In the present study HELLP syndrome was seen in 1.50% of the thrombocytopenic women which was statistically similar to the study by Turgot et al (1.14%), Habas et al (0.37%) and Vyas et al (4.08%). 9,18,19,30 Whereas studies by Parnas et al and Onisai et al showed HELLP syndrome in 12.06% and 9.52% women respectively, which was higher than our study. 13,21 In present study incidence of ITP was 3% amongst pregnant thrombocytopenic women.…”
Section: 17contrasting
confidence: 78%
“…23,28 [9][10][11]14,21 In the present study HELLP syndrome was seen in 1.50% of the thrombocytopenic women which was statistically similar to the study by Turgot et al (1.14%), Habas et al (0.37%) and Vyas et al (4.08%). 9,18,19,30 Whereas studies by Parnas et al and Onisai et al showed HELLP syndrome in 12.06% and 9.52% women respectively, which was higher than our study. 13,21 In present study incidence of ITP was 3% amongst pregnant thrombocytopenic women.…”
Section: 17contrasting
confidence: 78%
“…Platelet indices such as platelet count, MPV, plateletcrit, and PDW are important indicators of platelet activation and thromboembolic events. Thrombocytopenia may be a late laboratory finding of preeclampsia, and low levels are usually associated with more severe disease (22) . However, several studies have reported that first trimester platelet count might not be a good marker to predict subsequent preeclampsia (12,23) .…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports our study. 21 Heilmann et al has reported that non-significant changes were observed in values of plasma viscosity, white cells, platelets, haptoglobin, MCHC, reticulocytes, triglycerides and cholesterol. This finding partially support our study.…”
Section: Discussionmentioning
confidence: 99%